Life-threatening Pneumocystis jiroveci Pneumonia with Cytomegalovirus Coinfection in a Follicular Lymphoma Patient During Rituximab-based Chemotherapy - Mu-Chun Yang; Sheng-Kang Chiu; Jong-Kai Hsiao; Woei-Yau Kao (Journal of Cancer Research and Practice)
In the era of target therapy, we face the challenge of the risk of opportunistic infection in patients with B-cell lymphoma who receiving rituximab-based chemotherapy. Opportunistic infections such as Pneumocystis jiroveci pneumonia (PJP) and Cytomegalovirus (CMV) pneumonia are life-threatening diseases. However, PJP with CMV coinfection is rare. Here, we report a follicular lymphoma patient who suffered from PJP with CMV coinfection after receiving three cycles of rituximab, cyclophosphamide, vincristine, and prednisone regimen and was successfully rescured after timely identification and treatment. We emphasize that physicians should be alert for the coinfection of PJP and CMV in lymphoma patients receiving rituximab-based chemotherapy and the timely recognition, and treatment that may avoid a deadly outcome.